Pengaruh Kemandirian Belajar Terhadap Hasil Belajar Matematika Di SDN 2 Singocandi - Fazriani, Hesty Nur; Wulandari, Kurnia; Frasida, Sofa Amalia (LPPM Universitas Advent Indonesia, 2024)
This study aims to identify the influence and how much influence between learning independence on student math learning outcomes. This type of research uses quantitative research and the analysis technique used is simple linear regression. The population in this study were 6th grade students at SDN 2 Singocandi with a sample of 23 students. The instrument used is that the researcher makes a questionnaire for student learning independence data, and gives test questions to measure student learning outcomes. The results of the analysis show that the average score is greater than the standard which indicates that the distribution of the data variables is small or there is no considerable gap from the lowest and highest ROA ratios. After the data was collected, a simple linear regression test was carried out with the prerequisites of normality test and linearity test between the variables of learning independence and students' math learning outcomes. The results of this study indicate the effect of learning independence on student learning outcomes by 88.5%. So it can be concluded that learning independence has a positive and significant influence on student math learning outcomes. The higher the learning independence, the higher the math learning outcomes.